Microorganisms: the secret agents of the biosphere, and their key roles in biotechnology - Oliveira, Valeria Maia; Andreote, Fernando Dini; Cortelo, Patricia Cardoso; Castro-Gamboa, Ian [UNESP]; Costa-Lotufo, Leticia V.; Polizeli, Maria de Lourdes T. M.; Thiemann, Otávio H.; Setubal, João Carlos (FapUNIFESP (SciELO), 2022)
We present a survey of projects that have been funded by FAPESP under the BIOTA-Microorganisms program. These projects generated a wide variety of results, including the identification of novel antibacterialproducing microorganisms, the characterization of novel microbial enzymes for industrial applications, taxonomic classification of novel microorganisms in several environments, investigation of the soil and mangrove microbial ecosystems and its influence on endangered plant species, and the sequencing of novel metagenome-assembled genomes. The results surveyed demonstrate the importance of microorganisms in environments that play important roles in human activities as well as the potential that many of these microorganisms have in contributing to biotechnological applications crucial for human survival in the 21st century.
Micro-organismos: os agentes secretos da biosfera, e seus papéis determinantes na biotecnologia
Keywords: bioprospecting; enzymes; metagenomics; Microbial diversity; microbiome; secondary metabolites